Sustainable Development Between Myth and Reality: European Perspectives - Kristina Jovanova, Natalija Nikolovska (European Journal of Sustainable Development, 2017)
In reaction to the consequences of the global capitalism development in the years after 1990s, the challenges of sustainable development became one of the top subjects among scientists. In the UN resolution: “Transformation of our World: 2030 Sustainable Development Agenda” the responsibility of the global community and the necessity of each nation state to participate and contribute to resolving the key cumulated problems of the economic, social and environmental development is emphasized. The analysis will elaborate related controversies, dilemmas and identified crisis of the sustainable development concept, demonstrated through demystification of the neoclassical paradigms and extreme neoliberal monism, being unsustainable as such. The global scene is witnessing processes that are leading towards changes in the development paradigm. They are reflected in the shift from the domination of the unipolar neoliberal model to polycentric structures of the capitalist order, giving room to competitiveness of different models of capitalism. The need for the European Union to act proactively and affirm the EU model of social-market capitalism will be underlined. It incorporates a vast spectrum of different sustainable development concept dimensions, but nevertheless, needs redefining for better positioning within the new global order. Keywords: Sustainable development, neoliberalism, global economy, European Union, social- market capitalism